Dukungan untuk Wanita Penyandang Disabilitas pada Akun Instagram @lipstickuntukdifabel - Dinar Asvi Nurjannah; Yasinta Putri Wijaya; Fakri Reza K (Ridwan Institute, 2021)
The purpose of this research is to dissect the Agenda Setting conducted by Instagram social media @lipsticuntukdifabel in order to support women with disabilities. This study uses agenda setting theory in analyzing the findings contained in this research. the results showed thatpeople with disabilities often assume that their shortcomings make them different from others. This often leads to a lack of confidence in people with disabilities, especially in their social environment, some people with disabilities tend to withdraw from social interactionsdue to lack of confidence. Various confidence supporting tools such as makeup become very important to be used in creating confidence for people with disabilities. In addition, factors fromoutside the social environment pa rapeople withdisabilities become an important factor insupportingthe confidence of people with disabilities